Excavations at Glasgow Cathedral 1988-1997 - Driscoll, Stephen T., author.
1 online resource (188 pages)
Keywords: In 1988 extensive archaeological investigations began at Glasgow Cathedral revealing evidence for the first cathedral built in 1136 and subsequent 12th century phases.